Finding the flow (approach training and practice) - Dellemann, M. (Techniques Magazine, 2023)
Coaches tend to be more invested in certain aspects of an event thatn others. As the jumps coach at Northern Michigan University, I am most passionate about the horizontal jumps apporacht. My athletes and I spend significant time developing their approaches, including proper sprint mechanics, step count, flow and approach theory. An athlete cannot have a great jump with a poow approach. My coaching journey has also progressed throughout the years, going from simple to complex and back to simple again. In the beginning, my experience in coaching jumps was limited compared to my experience with speed, strength and running mechanics. The athletes I coached spent some time jumping, but more time sprinting and in the weight room. Besides making them better jumpers, I also wanted to make them better overall athletes. A few talented freshmen thrived in my first year of coaching with this mentality, including a female jumper who improved from 5.30 meters to 5.70 meters, and a male triple jumper who improved a full meter. As the years passed, I thought I understood more about the event and my training philosophy became complex. My training library became vast; day-to-day drills and activities changed up frequently with litte continuity, resulting in the athletes never truly mastering them. Unfortunately, the progeess seemed to stall, and the athletes had a harder time grasping what they were trying to do. Nowadays, I am back to training simply, doing drills and exercises that resemble the jumps as closely as possible. I back this up by doing speed work and other training that may not directly link to the event but achieves the now secondary goal of becoming better overall athletes. A good jump starts with a solid apporach, from the initial step through the penultimate step. All of the jumpers I´ve coached to date have stuck with the traditional eight-step (eight elft oder right, 16 total) approach. Through this article, I break down my approach training into three phases - the drive, the build, and the attack with a traditional eight-step approach. I point out common errors and my teach-and-train philosophy for each phase of the approach.